The Internalization of Moderate Islamic Values in Islamic Religious Education (PAI) Learning and Its Implications for Social Attitudes in Schools - Hasan Khariri; Ilman Nafi'a; Akhmad Affandi; Iwan Iwan (Jurnal Pendidikan Terapan, 2026)
The increasing intolerance, student violence, and brawls in Indonesia indicate serious challenges in shaping the character of the younger generation, particularly within the school environment. This study aims to describe the process of internalizing moderate Islamic values in Islamic Religious Education (PAI) learning and its implications for the development of students’ social attitudes. This study employs a descriptive analysis method with a literature review approach, utilizing various secondary sources such as journals, books, news, and related official documents. The results of the study indicate that the internalization of moderate Islamic values, which include tawassuth, tawazun, i’tidal, tasamuh, musawah, syura, islah, awlawiyah, qudwah, and tahadhur, can strengthen students’ character in three main dimensions: cognitive awareness, affective appreciation, and behavioral manifestation. This process is in line with the theories of Vygotsky and Bandura, which emphasize the importance of learning through social interaction, exemplification, and modelling. The implementation of moderate values in PAI has implications for the improvement of positive social attitudes, such as tolerance, cooperation, justice, and respect for differences, which become essential capital in preventing conflicts among students and strengthening social harmony in schools. This study recommends strengthening a religious moderation-based PAI curriculum, teacher training in contextual approaches, and the creation of a conducive learning environment to support the sustainable process of internalizing moderate Islamic values.